Understanding physical developer (PD): Part I – Is PD targeting lipids?. (December 2015) - de la Hunty, Mackenzie; Moret, Sébastien; Chadwick, Scott; Lennard, Chris; Spindler, Xanthe; Roux, Claude
Highlights: Investigation into the chemical targets of physical developer. Common epidermal lipid standards did not develop with physical developer. Fingermarks still develop with physical developer after lipid removal. Physical developer may target eccrine constituents in fingermark residue. Abstract: Physical developer (PD) is a fingermark development technique that involves the selective reduction of silver onto fingermark residue. PD can develop marks on porous substrates even if they have been wet, leading to the logical, long held belief that the reagent targets the water insoluble constituents in the fingermark residue. The present research has tested this hypothesis as part of a broader study that aims to identify the targets of physical developer. Spot tests of some fatty acids, cholesterol and squalene, treated with PD, showed that only cholesterol produced significant silver deposition. PD is known to be particularly effective on aged marks, however cholesterol degrades over time. These observations indicate that PD reactivity with fingermarks cannot solely be due to the presence of cholesterol. Fingermarks were deposited on paper and washed with various organic solvents before being treated with PD. PD effectiveness was intermittent on both solvent washed and unwashed sides of both natural and groomed marks; however, it was seen to effectively develop groomed samples that had been exposed to common lipid extraction solvents, shown to have removed the lipids by visualisation using the lipid stain Nile red. PD effectiveness was most affected by exposure of samples to solvents that could dissolve water soluble components, showing that the removal of these constituents (by either water, or other solvents) decreases the amount of silver deposited on the fingermark residue by the working solution. Close observation of PD developed samples showed variation in silver deposition uniformity when comparing a developed ridge to a pore site located on that ridge. Some samples showed an absence of silver, and other showed an increase of silver at pore locations. This indicates that the material excreted by the pores on the finger has an effect on silver deposition, suggesting that PD may be specifically targeting eccrine constituents that are present along the ridges but are more concentrated at the pore locations. These findings indicate that PD is not targeting the lipids in the fingermark residue per se, and may instead be targeting eccrine constituents or a more complex mixture of both eccrine and lipid constituents. Further investigation is underway within our group to investigate the components targeted by PD to gain a better understanding of what is a notoriously sensitive and hard to employ technique in the hope that it can be improved or simplified, or alternatives identified.